2021
DOI: 10.1088/1748-605x/ac2885
|View full text |Cite
|
Sign up to set email alerts
|

Novel transdermal bioadhesive surfactant-based system for release and solubility improvement of antimalarial drugs artemether-lumefantrine

Abstract: Artemether (ART) and lumefantrine (LUM) are the gold standard antimalarial drugs used for the treatment of malaria in children and pregnant women. Typically, ART and LUM are delivered orally in the form of a combined tablet, however, the appropriateness of this route of administration for these drugs is questionable due to the poor absorption and therefore bioavailability observed unless administered alongside lipid-rich foods. Transdermal drug delivery in the form of a patch-type system has been identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…Many new antimalarial combination therapy studies have been reported towards the goal of overcoming ACT-resistant P. falciparum , including derivatives of artemisinin with other compounds, but despite these efforts, the resistance of P. falciparum to ACT remains increasing in prevalence [ 18 , 19 ]. Antimalarial drug development studies for children using artemisinin derivatives were also reported [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many new antimalarial combination therapy studies have been reported towards the goal of overcoming ACT-resistant P. falciparum , including derivatives of artemisinin with other compounds, but despite these efforts, the resistance of P. falciparum to ACT remains increasing in prevalence [ 18 , 19 ]. Antimalarial drug development studies for children using artemisinin derivatives were also reported [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lyotropic LCs (or lyomesophases) consisting of amphiphiles have a tendency to form self-assembled structures depending on their concentration in solution. The physicochemical properties of lyotropic LCs and their intrinsic structures, including lamellar, hexagonal, and cubic phases, make them suitable as drug delivery agents in pharmaceutical sciences in a wide range of applications [ 11 , 12 , 13 , 14 , 15 , 16 ]. In particular, the hexagonal and cubic phases are of high interest in the field of drug delivery agents owing to their ability to control or maintain the release of hydrophilic and hydrophobic drug molecules with a wide range of molecular weights [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%